The case of the Hudson's Bay Company [electronic resource] : in a letter to Lord Palmerston - Freeport, Andrew; Palmerston, Henry John Temple, Viscount, 1784-1865. (London : E. Stanford, 1857)
Table. Electronic reproduction. Mode of access: Internet. 44